How to modify test items for ELLs: What research says (Part 2 of 3) (pp. 16--24) - Norval, Brooke (Ohio Journal of School Mathematics, 2019)
The following is the second installment in a three-part series exploring ways to modify mathematics tasks to make them more equitable for English language learners (ELLs). In this second installment, the author summarizes the existing research literature, uncovering strategies for modifying mathematics test items linguistically.